Relationship between Classroom Management and Students Academic Achievement: Muhammad Nisar, Iqbal Amin Khan, Faridullah Khan (PJDOL, 2023)
It is evident that teachers who organize and manage classroom properly will assist students’ learning. This study focuses about the association and connection between the classes managing practices and activitiesused by secondary school teachers and the students’ academic achievement. Correlational research design was used for this study. Asample of 550 secondary school teachers was selected conveniently from50 government schools of district Kohat. A self-constructed questionnaire based on five-point rating scale was used for collection of data. Mean, standard deviation and co-efficient of correlation was used to analyze the data. It was found that secondary school teachers used moderate to high level of classroom management practices. Managing physical resources had the highest mean score while managing students’ behavior and teaching methodology had the lowest mean score. Good relationship between teacher’s practices and learner’s achievement was found as a vital and basic element for the school high academic scores.